Evaluation of standard diagnostic rapid test kits for malaria diagnosis among HIV patients in Kano, Nigeria - Henry A. Mbah; Feyisayo E. Jegede; Surajudeen A. Abdulrahman; Tinuade I. Oyeyi (AOSIS, 2018)
Background: Malaria diagnosis among HIV-positive patients is uncommon in Nigeria despite the high burden of both diseases. Objectives: We evaluated the performance of a malaria rapid diagnostic test (MRDT) against blood smear microscopy (BSM) among HIV-positive patients in relation to anti-retroviral treatment (ART) status, CD4+ count, fever, cotrimoxazole prophylaxis and malaria density count. Method: A cross-sectional study involving 1521 consenting randomly selected HIV-positive adults attending two ART clinics in Kano, Nigeria, between June 2015 and May 2016. Venous blood samples were collected for testing with MRDT, BSM, and CD4+ T cells count by cytometry. Biodata and other clinical details were extracted from patient folders into an Excel file, cleaned, validated, and exported for analysis into SPSS version 23.0. Sensitivity, specificity, predictive values of MRDT were compared with BSM with a 95% confidence interval. Results: Malaria parasites were detected in 25.4% of enrollees by BSM and 16.4% by MRDT. Overall sensitivity of MRDT was 58% and specificity was 97%. Cotrimoxazole prophylaxis and fever status did not affect MRDT sensitivity and specificity. Unexpectedly, the sensitivity was highest at parasite density count of less than 500 cells/µL. At CD4+ T cells count over 500 cells/µL the sensitivity was higher (62.4%) compared to 56% at less than 500 cells/µL. In the non-ART group sensitivity was higher (65%) compared to those on ART (56%) but the specificity was similar. All differences were significant for all variables (p < 0.05). Conclusion: Although the MRDT specificity was good, the sensitivity was poor, requiring further evaluation for use in malaria diagnosis among HIV-malaria co-infected persons in these settings.